Candicidin Isomer Production Is Essential for Biocontrol of Cucumber Rhizoctonia Rot by Streptomyces albidoflavus W68 - Yao, Xueyan (Appl Environ Microbiol, 2021)
Diseases caused by soilborne fungal pathogens result in significant crop yield losses and quality reduction. Streptomyces albidoflavus strain W68 is effective in controlling several soilborne fungal diseases. To identify antifungal substances critical for biocontrol activity of W68, the genome of W68 was sequenced and a linear chromosome of 6.80 Mb was assembled. A total of 21 secondary metabolite biosynthesis gene clusters (BGCs), accounting for 12.27% of the genome, were identified. Core gene deletion mutants for each of all 8 BGCs for nonribosomal peptide synthetases and polyketide synthases were created. Among them, only the mutant lacking ctg1-5755 (the gene was renamed as fscD(W68)) in BGC 19, which shares 100% sequence similarity with the BGC for candicidin synthesis, showed obvious reduction in antifungal activity. A pot experiment revealed that biocontrol effects of the ΔfscD(W68) mutant in Rhizoctonia rot of cucumber were also significantly compromised relative to W68. Liquid chromatography-mass spectrometry (LC-MS) analysis revealed that W68 but not the ΔfscD(W68) mutant can produce candicidin isomers, indicating that the production of candicidin isomers is key for antifungal activity and biocontrol activity of S. albidoflavus W68. IMPORTANCE This study reports that candicidin-like secondary metabolites produced by microbial cells in natural soil environments can effectively control soilborne fungal diseases, revealing a novel mechanism of microbial biocontrol agents. We demonstrated that the main antifungal activity and biocontrol activity of Streptomyces albidoflavus strain W68 are attributable to the production of candicidin isomers, suggesting that gene clusters for candicidin-like compound biosynthesis might be used as molecular markers to screen and breed microbial strains for biocontrol agent development.